Transition metal element doped two-dimensional ruthenium oxide electrolyzed water catalyst and preparation method thereof

By introducing transition metal elements into Ru-based materials, the doped two-dimensional ruthenium oxide electrolytic catalyst is solved, and the catalytic activity and corrosion resistance of existing Ru-based materials are achieved, efficient OER catalysis and stability are achieved, and the preparation process is simplified.

CN119843313APending Publication Date: 2025-04-18NORTH CHINA POWER ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411802791.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When existing Ru-based materials are used as anode catalysts, electrocatalytic activity and corrosion resistance are difficult to meet the needs, and the preparation process is complicated.

Method used

A two-dimensional ruthenium oxide electrolytic catalyst doped with transition metal elements is used to form a doped structure by introducing transition metal elements such as manganese, iron, cobalt, nickel, copper, zinc, etc. into the Ru-based material, and the electronic structure of the catalyst is optimized, and synthesized by a simple molten salt method.

Benefits of technology

The excellent OER catalytic activity and stability of the catalyst are achieved, the overpotential of the OER is reduced, the corrosion resistance of the catalyst is improved, the preparation process is simplified, and the utilization efficiency of Ru is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843313A_ABST
    Figure CN119843313A_ABST
Patent Text Reader

Abstract

The invention discloses a transition metal element doped two-dimensional ruthenium oxide electrolyzed water catalyst and a preparation method thereof, the morphology of the catalyst is a lamellar structure, the doped transition metal element is one of manganese, iron, cobalt, nickel, copper and zinc, and the doping amount is not more than 20%. The ruthenium element and the transition metal element in the catalyst interact with each other, the internal electronic structure of the catalyst is optimized, the morphology of the catalyst is of a lamellar structure, the electrochemical active area of the catalyst is increased, and therefore the overpotential of OER is greatly reduced; the doped two-dimensional ruthenium oxide nanosheet, as an electrocatalyst of OER, can be kept stable and not corroded during oxygen evolution, so that the stability of the ruthenium-based catalyst is improved, and the ruthenium-based catalyst can be applied to catalytic oxygen evolution reaction in an acid environment; the manufacturing process is simple and easy to implement and has the potential of large-scale production. Therefore, the method has relatively high economic benefits and application values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water electrolysis catalysts, and specifically relates to a transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst and a preparation method thereof. Background Art

[0002] At present, renewable energy is developing rapidly, but due to the intermittent, volatile and random characteristics of renewable energy, the effective consumption of renewable energy is a problem. Hydrogen has the characteristics of high energy density, rich application scenarios, clean and efficient, and water electrolysis technology has a certain degree of operational flexibility. Therefore, using renewable energy to drive water electrolysis equipment to produce hydrogen can effectively consume renewable energy. At present, the water electrolysis hydrogen production technologies with mature market applications are mainly proton exchange membrane water electrolysis hydrogen production technology and alkaline water electrolysis hydrogen production technology. Compared with alkaline water electrolysis technology, proton exchange membrane water electrolysis hydrogen production technology has better performance, with the characteristics of high current density, low ohmic loss, high gas purity, strong flexibility, etc., and is more suitable for renewable energy.

[0003] In the proton exchange membrane water electrolysis technology, the hydrogen evolution reaction occurring at the cathode is a two-electron transfer process with rapid kinetics. In contrast, the reaction occurring at the anode is a four-electron transfer oxygen evolution reaction (OER), which has slow kinetics. Therefore, the anode catalyst must have extremely high electrocatalytic activity to improve the kinetics of OER. When electrolyzing water, the anode will be subjected to a high oxidation potential and the local environment is acidic, which is very easy to be corroded. Therefore, the anode catalyst also needs to have excellent corrosion resistance in this working environment. Currently, the commonly used anode catalyst materials are mainly iridium (Ir)-based materials and ruthenium (Ru)-based materials, both of which are difficult to meet the above requirements. Compared with Ir-based materials, Ru-based materials have lower costs, higher activities, and better application prospects, but their stability is biased.

[0004] In summary, when designing Ru-based materials as anode catalysts, the catalytic activity and stability of the Ru-based catalysts should be improved, and the preparation process should be simple and easy. Based on this, the present invention is proposed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a two-dimensional ruthenium oxide water electrolysis catalyst doped with a transition metal element and a preparation method, so as to solve the problem that the electrocatalytic activity and corrosion resistance of the existing catalysts are difficult to meet the requirements, and to achieve excellent OER catalytic activity and stability. The preparation process is simple and easy, and the utilization efficiency of the precious metal Ru in the catalyst is greatly improved.

[0006] According to the technical solution of the present invention, the present invention provides a two-dimensional ruthenium oxide water electrolysis catalyst doped with a transition metal element, whose morphology is a lamellar structure, and the doped transition metal element is one of manganese, iron, cobalt, nickel, copper, and zinc, and the doping amount is not more than 20%.

[0007] Preferably, it is nickel-doped two-dimensional ruthenium oxide, which has a -2 The overpotential is 208mV.

[0008] Preferably, it is nickel-doped two-dimensional ruthenium oxide, which has a -2 The catalytic activity was stable for 100 h.

[0009] Preferably, it is used to catalyze oxygen evolution reaction in an acidic environment.

[0010] According to the technical solution of the present invention, the present invention also provides a method for preparing a transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst, which is used to prepare the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst of the present invention, and comprises the following steps: Step S1, adding sodium nitrate, a ruthenium salt precursor, and a transition metal salt precursor to ultrapure water, and obtaining a solution after ultrasonic treatment; Step S2, evaporating and drying the solution obtained in step S1 to obtain a black solid; Step S3, heat-treating the solid obtained in step S2 to obtain a black solid; Step S4, after cooling, placing the black solid obtained in step S3 in ultrapure water, and after the sodium nitrate therein is dissolved, collecting the product by centrifugation; after collection, washing it with ultrapure water three times to obtain a black solid powder; Step S5, placing the black solid powder collected in step S4 in 0.5M sulfuric acid to remove the unstable part; Step S6, collecting the product after step S5 by centrifugation, washing the obtained product with ultrapure water, and drying to obtain the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst.

[0011] Furthermore, in step S1, the ruthenium salt precursor is one or a combination of anhydrous ruthenium trichloride and ruthenium trichloride hydrate, and the transition metal salt precursor is one or a combination of manganese dichloride, ferric chloride, cobalt dichloride, nickel dichloride, copper dichloride, and zinc dichloride.

[0012] Furthermore, in step S2, evaporation to dryness is evaporation to dryness under an oil bath.

[0013] Furthermore, in step S2, the evaporation and drying temperatures are both 40°C to 60°C, and the evaporation and drying times are both 8h to 12h.

[0014] Furthermore, in step S3, the heat treatment is performed in a muffle furnace to convert the sodium nitrate into a liquid state, and the ruthenium salt precursor and the transition metal salt precursor are oxidized into oxides in an air atmosphere.

[0015] Furthermore, in step S3, the heat treatment temperature is 350° C. and the time is 2 h.

[0016] Compared with the prior art, the beneficial technical effects of the present invention are as follows: 1. There is interaction between the ruthenium element and the transition metal element in the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst of the present invention, which optimizes the internal electronic structure of the catalyst, and the catalyst morphology is a lamellar structure, which increases the electrochemical active area of ​​the catalyst, thereby greatly reducing the overpotential of OER.

[0017] 2. The transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst of the present invention is a doped two-dimensional ruthenium oxide nanosheet. As an electrocatalyst for OER, it can remain stable during oxygen evolution and is not corroded, thereby improving the stability of the ruthenium-based catalyst.

[0018] 3. The transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst of the present invention is synthesized by a simple molten salt method, with low equipment cost and operation cost, and is easy to realize industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the XRD pattern of the catalyst prepared in Example 1 of the present invention.

[0020] Figure 2 This is the TEM spectrum of the catalyst prepared in Example 1 of the present invention.

[0021] Figure 3 This is a graph of the catalytic activity of the catalyst prepared in Example 1 of the present invention in oxygen evolution reaction in 0.5M H2SO4 measured by linear voltammetric scanning in a three-electrode system.

[0022] Figure 4 This is a graph of the catalytic stability of the catalyst prepared in Example 1 of the present invention in the oxygen evolution reaction in 0.5MH2SO4 measured by chronopotentiometry in a three-electrode system. DETAILED DESCRIPTION

[0023] The present invention provides a transition metal element doped two-dimensional ruthenium oxide electrolysis catalyst and a preparation method, more specifically an anode catalyst used in proton exchange membrane water electrolysis technology, which solves the problem that the electrocatalytic activity and corrosion resistance of existing catalysts are difficult to meet the needs, and achieves excellent OER catalytic activity and stability, and the preparation process is simple and easy, which greatly improves the utilization efficiency of the precious metal Ru in the catalyst. One of the embodiments of the transition metal element doped two-dimensional ruthenium oxide is nickel-doped two-dimensional ruthenium oxide. The present invention introduces transition metal elements in the preparation process of ruthenium-based catalysts, optimizes the electronic structure of the catalyst through the interaction between elements, and the two-dimensional morphology prepared by the molten salt method increases the electrochemical active surface area of ​​the catalyst, thereby greatly improving the activity of the catalyst; the introduction of transition metal elements also improves the stability of ruthenium oxide; the manufacturing process is simple and easy, and has the potential for large-scale production. Therefore, the present invention has high economic benefits and application value.

[0024] The technical solution of the present invention will be further described below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.

[0025] Example 1 Step S1, adding sodium nitrate, a ruthenium salt precursor, and a transition metal salt precursor to ultrapure water, and obtaining a solution after ultrasonic treatment; specifically, adding 1 g of sodium nitrate to 5 mL of ultrapure water to dissolve, and then adding 0.3 mmol of hydrated ruthenium chloride and 0.1 mmol of nickel dichloride, and obtaining a uniform solution after ultrasonic treatment for 0.5 h; Step S2, evaporating and drying the solution obtained in step S1 to obtain a black solid; specifically, evaporating the solution in an oil bath at 60° C. for 12 hours, and then placing it in a blast oven at 60° C. and drying it for 12 hours to obtain a black solid.

[0026] Step S3, heat-treating the solid obtained in step S2 to obtain a black solid; specifically, placing the solid in a muffle furnace for calcination heat treatment at a heating rate of 10°C min -1 , the heat treatment temperature is raised to 350°C, and the calcination time is 2 hours. The heat treatment process turns the sodium nitrate into liquid, and the ruthenium salt precursor and the transition metal salt precursor are oxidized into oxides in an air atmosphere, thereby obtaining a black solid powder, which is a mixture of nickel-doped two-dimensional ruthenium oxide and sodium nitrate.

[0027] Step S4, after cooling, placing the black solid obtained in step S3 in ultrapure water, and after the sodium nitrate therein is dissolved, collecting the product by centrifugation, and washing it three times with ultrapure water after collection to obtain a black solid powder; specifically, the rotation speed during centrifugation is 10000 rpm.

[0028] Step S5, placing the black solid powder collected in step S4 in 0.5M sulfuric acid for a period of time to remove unstable parts of the catalyst; specifically, placing the black solid powder in 0.5M sulfuric acid at 60°C for 8 hours.

[0029] Step S6, centrifugally collecting the product after step S5, washing the product again with ultrapure water, and drying to obtain the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst; specifically, centrifugally collecting the product of step S5 at a speed of 10000 rpm, washing the product of step S5 again with ultrapure water, and drying at 60°C to obtain the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst.

[0030] The crystal structure of the catalyst material prepared above is Figure 1 The XRD diffraction spectrum of the catalyst material can be determined to be a tetragonal system, with obvious diffraction peaks corresponding to each crystal plane and good crystallinity. Figure 2 The TEM photos in the figure show that the morphology is lamellar and the size of the lamellar is at the micron level.

[0031] The above method of the present invention is used to obtain the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst of the present invention, which has a lamellar structure, and the doped transition metal element is nickel (combined with other embodiments, the doped transition metal element is one of manganese, iron, cobalt, nickel, copper, and zinc), and the doping amount is not more than 20%.

[0032] Example 2 The preparation steps and conditions are basically the same as those in Example 1, except that the nickel dichloride in step S1 is replaced by an equal amount of zinc dichloride.

[0033] Example 3 The preparation steps and conditions are basically the same as those in Example 1, except that the nickel dichloride in step S1 is replaced by an equal amount of ferric chloride.

[0034] In some embodiments, in step S1, the ruthenium salt precursor is one or more of anhydrous ruthenium trichloride and ruthenium trichloride hydrate, and the transition metal salt precursor is one or more of manganese dichloride, ferric chloride, cobalt dichloride, nickel dichloride, copper dichloride, and zinc dichloride. In step S2, the evaporation and drying temperatures are both 40°C to 60°C, and the evaporation and drying times are both 8h to 12h.

[0035] Application Example 1 The catalyst material (doped two-dimensional ruthenium oxide, i.e., two-dimensional Ni-RuO2) obtained in Example 1 of the present invention was used to catalyze the oxygen evolution reaction in an acidic electrolyte. In a three-electrode test system, a graphite rod was selected as a counter electrode, silver / silver chloride was selected as a reference electrode, and 0.5 mol L -1H2SO4 is the electrolyte. The test process includes the following contents.

[0036] 1. Take 10 mg of the catalyst material (supported catalyst) obtained in Example 1 and add it to 5 mL of a mixed solvent of water and isopropanol (1:1), then drop 50 μL of Nafion solution (5 wt%), and ultrasonicate for 30 min to form a uniform catalyst ink. Then take a certain amount of ink and evenly drop it on a glassy carbon rotating disk electrode with a diameter of 5 mm. After drying, use it as a working electrode for testing. The loading capacity is 0.2 mg cm -2 , the disc speed in the test was 1600rpm.

[0037] 2. The electrocatalytic oxygen evolution performance of the catalyst obtained in Example 1 of the present invention was tested by linear voltammetric scanning method, and the linear voltammetric scanning rate was 5 mV s -1 , potential range 1.35V-1.75V (vs. RHE).

[0038] 3. The stability of the catalyst obtained in Example 1 of the present invention was tested by chronopotentiometry, where the current density was set to 10 mA cm -2 .

[0039] The test results show that the catalytic activity of the catalyst material prepared above is good, reaching 10 mA cm in 0.5 M H2SO4 solution. -2 The overpotential required for the current density is only 208mV. The catalyst material prepared above has good catalytic stability and can reach 10mA cm -2 At a current density of 1.5 Å, the catalytic activity can be maintained for more than 100 h.

[0040] In summary, there is an interaction between the ruthenium element and the transition metal element in the catalyst of the present invention, which optimizes the internal electronic structure of the catalyst, and the catalyst morphology is a lamellar structure, which increases the electrochemical active area of ​​the catalyst, thereby greatly reducing the overpotential of OER; the doped two-dimensional ruthenium oxide nanosheets, as an electrocatalyst for OER, can remain stable during oxygen evolution and not be corroded, thereby improving the stability of ruthenium-based catalysts and can be used to catalyze oxygen evolution reactions in acidic environments; the present invention is synthesized by a simple molten salt method, with low equipment cost and operating cost, and is easy to achieve industrial mass production.

[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention; for ease of description, only the parts related to the relevant inventions are shown in the accompanying drawings. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other; modifying the technical solutions recorded in the aforementioned embodiments, or replacing some of the technical features therein by equivalents, does not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A transition metal element doped two-dimensional ruthenium oxide water electrolysis catalyst, characterized in that: Its morphology is a lamellar structure, and the doped transition metal element is one of manganese, iron, cobalt, nickel, copper, and zinc, and the doping amount is not more than 20%.

2. The transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst according to claim 1, characterized in that: It is a two-dimensional ruthenium oxide doped with nickel, which has a high -2 The overpotential is 208mV.

3. The transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst according to claim 1, characterized in that: It is a two-dimensional ruthenium oxide doped with nickel, which has a high -2 The catalytic activity was stable for 100 h.

4. The transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst according to claim 1, characterized in that: It is used to catalyze oxygen evolution reaction in acidic environment.

5. A method for preparing a transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst, characterized in that: The method is used for preparing a two-dimensional ruthenium oxide water electrolysis catalyst doped with a transition metal element according to any one of claims 1 to 4, and comprises the following steps: Step S1, adding sodium nitrate, a ruthenium salt precursor, and a transition metal salt precursor to ultrapure water, and obtaining a solution after ultrasonic treatment; Step S2, evaporating and drying the solution obtained in step S1 to obtain a black solid; Step S3, heat-treating the solid obtained in step S2 to obtain a black solid; Step S4, after cooling, placing the black solid obtained in step S3 in ultrapure water, and after the sodium nitrate therein is dissolved, collecting the product by centrifugation; after collection, washing it with ultrapure water three times to obtain a black solid powder; Step S5, placing the black solid powder collected in step S4 in 0.5M sulfuric acid to remove the unstable part; Step S6, collecting the product after step S5 by centrifugation, washing the obtained product with ultrapure water, and drying to obtain the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst.

6. The method for preparing the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst according to claim 5, characterized in that: In step S1, the ruthenium salt precursor is one or a combination of anhydrous ruthenium trichloride and ruthenium trichloride hydrate, and the transition metal salt precursor is one or a combination of manganese dichloride, ferric chloride, cobalt dichloride, nickel dichloride, copper dichloride, and zinc dichloride.

7. The method for preparing the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst according to claim 5, characterized in that: In step S2, evaporating to dryness is evaporating to dryness under an oil bath.

8. The method for preparing the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst according to claim 5, characterized in that: In step S2, the evaporation and drying temperatures are both 40° C. to 60° C., and the evaporation and drying times are both 8 h to 12 h.

9. The method for preparing the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst according to claim 5, characterized in that: In step S3, the heat treatment is performed in a muffle furnace to convert the sodium nitrate into liquid, and the ruthenium salt precursor and the transition metal salt precursor are oxidized into oxides in an air atmosphere.

10. The method for preparing the transition metal element-doped two-dimensional ruthenium oxide water electrolysis catalyst according to claim 9, characterized in that: In step S3, the heat treatment temperature is 350° C. and the time is 2 h.